Overview of meta‐analysis. Issue 1 (28th March 2021) - Fang, Xu; Zhao, Nan; Zhu, Zhao‐Qiong
Abstract : Meta‐analysis has been recognized as the best means to evaluate objectively and study the evidence for a particular issue. In order to give researchers a better understanding of the Meta process, we present an overall introduction to Meta‐analysis in terms of comprehensive assessment of the literature, goals, advantages, main steps, and article structure.